2020
DOI: 10.3390/molecules25184342
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, In Vitro and In Silico Studies of New Thiazolylhydrazine-Piperazine Derivatives as Selective MAO-A Inhibitors

Abstract: Monoamine oxidase (MAO) isoenzymes are very important drug targets among neurological disorders. Herein, novel series of thiazolylhydrazine-piperazine derivatives were designed, synthesized and evaluated for their MAO-A and -B inhibitory activity. The structures of the synthesized compounds were assigned using different spectroscopic techniques such as 1H-NMR, 13C-NMR and HRMS. Moreover, the prediction of ADME (Absorption, Distribution, Metabolism, Elimination) parameters for all of the compounds were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Molecular docking studies were performed using an in silico procedure to define the binding modes of the active compound ( 2l ) in the active regions of crystal structures of MAO-A (PDB ID: 2Z5X), retrieved from the Protein Data Bank server (, accessed 01 May 2021). Molecular docking studies were performed as previously reported. ,,,, …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular docking studies were performed using an in silico procedure to define the binding modes of the active compound ( 2l ) in the active regions of crystal structures of MAO-A (PDB ID: 2Z5X), retrieved from the Protein Data Bank server (, accessed 01 May 2021). Molecular docking studies were performed as previously reported. ,,,, …”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking studies were performed as previously reported. 31,39,45,55,56 4.6. Molecular Dynamics Simulation.…”
Section: Bbb Permeability Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, more than 40 piperazine-containing drugs have been FDA-approved as antianginals, antidepressants, antiserotonergics, urologicals, anthelmintics, antineoplastic agents, nootropics, and tranquillizers (Brito et al 2019). Furthermore, the substitution of one or both nitrogen atoms in the piperazine ring system with various structural motifs can result in significant MAO-A, MAO-B, and acetylcholinesterase (AChE) inhibitions (Pettersson et al 2012;Kaya et al 2017;Kumar et al 2018;Özdemir et al 2020;Sağlık et al 2020;Jevtić et al 2020;Modh et al 2013;Sahin et al 2018).…”
Section: Responsible Editor: Lotfi Aleyamentioning
confidence: 99%
“…[23] Some recent studies established that the incorporation of piperazine nucleus with other structural moieties is able to improve the interaction of the compounds with biological targets, and thereby improves the MAO inhibition properties. [14,21,[24][25][26][27][28][29][30] The unique class of enzymes known as monoamine oxidases (MAOs) is located in the mitochondria and is responsible for several biological processes. They are FAD-dependent and act as an essential catalyst in the oxidative deamination process for the metabolism of amine molecules.…”
Section: Introductionmentioning
confidence: 99%